Solar radiation induced skin damage: review of protective and preventive options - Svobodová, Alena; Vostálová, Jitka (International journal of radiation biology, 2010)
PURPOSE: Solar energy has a number of short- and long-term detrimental effects on skin that can result in several skin disorders. The aim of this review is to summarise current knowledge on endogenous systems within the skin for protection from solar radiation and present research findings to date, on the exogenous options for such skin photoprotection. RESULTS: Endogenous systems for protection from solar radiation include melanin synthesis, epidermal thickening and an antioxidant network. Existing lesions are eliminated via repair mechanisms. Cells with irreparable damage undergo apoptosis. Excessive and chronic sun exposure however can overwhelm these mechanisms leading to photoaging and the development of cutaneous malignancies. Therefore exogenous means are a necessity. Exogenous protection includes sun avoidance, use of photoprotective clothing and sufficient application of broad-spectrum sunscreens as presently the best way to protect the skin. However other strategies that may enhance currently used means of protection are being investigated. These are often based on the endogenous protective response to solar light such as compounds that stimulate pigmentation, antioxidant enzymes, DNA repair enzymes, non-enzymatic antioxidants. CONCLUSION: More research is needed to confirm the effectiveness of new alternatives to photoprotection such as use of DNA repair and antioxidant enzymes and plant polyphenols and to find an efficient way for their delivery to the skin. New approaches to the prevention of skin damage are important especially for specific groups of people such as (young) children, photosensitive people and patients on immunosuppressive therapy. Changes in public awareness on the subject too must be made.
Keywords: reaktivní formy kyslíku; pigmentace kůže; nádory kůže; Humans; Skin Neoplasms; melaniny; Skin Diseases; oprava DNA; Skin Pigmentation; reaktivní formy dusíku; Infrared Rays; kůže; lidé; Antioxidants; zvířata; sluneční záření; Reactive Nitrogen Species; ultrafialové záření; Reactive Oxygen Species; apoptóza; DNA Repair; přípravky chránící proti slunci; antioxidancia; kožní nemoci; Sunscreening Agents; Melanins; Ultraviolet Rays; Animals; Sunlight; Apoptosis; Skin; infračervené záření